H2 Stimulated Raman Scattering in a Multi-pass Cell with a Herriott Configuration - 蔡向龙 周灿华 周冬建 刘金波 郭敬为 贵林 (中国物理快报：英文版, 2015)
Stimulated raman scattering （SRS） is an effective method for expanding the spectral range of high power lasers, especially in the regime of near IR and middle IR. We report the SRS of high pressure H2 with a multiple-pass cell configuration. The SRS with the multiple-pass cell configuration is found to be very efficient for reduction of threshold of the first Stokes （S1）. Due to the coherent SRS （CSRS） process, the multiple-pass cell configuration is more effective for reduction of the threshold for the second Stokes （S2） SRS and for increasing the conversion efficiency of S2. This contributes to the relatively low conversion efficiency of S1 for the multiple-pass cell configuration. Multiple-pass cell SRS is also found to be very effective for improving the beam quality and the stability of S1.